The OPERA trial: a protocol for the process evaluation of a randomised trial of an exercise intervention for older people in residential and nursing accommodation - Parsons Suzanne; Taylor Stephanie JC; Ellard David R; Thorogood Margaret (Trials, 2011)
Abstract Background The OPERA trial is large cluster randomised trial testing a physical activity intervention to address depression amongst people living in nursing and residential homes for older people. A process evaluation was commissioned alongside the trial and we report the protocol for this process evaluation. Challenges included the cognitive and physical ability of the participants, the need to respect the privacy of all home residents, including study non-participants, and the physical structure of the homes. Evaluation activity had to be organised around the structured timetable of homes, leaving limited opportunities for data collection. The aims of this process evaluation are to provide findings that will assist in the interpretation of the clinical trial results, and to inform potential implementation of the physical activity intervention on a wider scale. Methods/design Quantitative data on recruitment of homes and individuals is being collected. For homes in the intervention arm, data on dose and fidelity of the intervention delivered; including individual rates of participation in exercise classes are collected. In the control homes, uptake and delivery of depression awareness training is monitored. These data will be combined with qualitative data from an in-depth study of a purposive sample of eight homes (six intervention and two control). Discussion Although process evaluations are increasingly funded alongside trials, it is still rare to see the findings published, and even rarer to see the protocol for such an evaluation published. Process evaluations have the potential to assist in interpreting and understanding trial results as well as informing future roll-outs of interventions. If such evaluations are funded they should also be reported and reviewed in a similar way to the trial outcome evaluation. Trial Registration ISRCTN No: ISRCTN43769277